2022
DOI: 10.3390/children9070978
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Children with Asthma

Abstract: A type-2 immune response usually sustains wheezing and asthma in children. In addition, dysbiosis of digestive and respiratory tracts is detectable in patients with wheezing and asthma. Probiotics may rebalance immune response, repair dysbiosis, and mitigate airway inflammation. As a result, probiotics may prevent asthma and wheezing relapse. There is evidence that some probiotic strains may improve asthma outcomes in children. In this context, the PROPAM study provided evidence that two specific strains signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 97 publications
2
5
0
Order By: Relevance
“…Moreover, the outcomes reported in AR were substantially consistent with what has been reported in the asthma model [52][53][54].…”
Section: New Evidence In the Literaturesupporting
confidence: 83%
“…Moreover, the outcomes reported in AR were substantially consistent with what has been reported in the asthma model [52][53][54].…”
Section: New Evidence In the Literaturesupporting
confidence: 83%
“…95 Moreover, administration of Lactobacillus taiwanensis to mice inhibits the expression of immunity to H. polygyrus, by promoting a strong Treg response. 96 Thus, interactions between probiotic bacteria and the immune system seem to impair anti-helminth immunity in many models, which is perhaps consistent with the effects described for some probiotics in suppressing symptoms of allergy and asthma [97][98][99] . Moreover, these results may imply that prebiotic dietary components that stimulate the production of lactobacilli or related bacteria may also have a similar attenuating effect on the type-2 response, with clear implications for probiotic supplementation in areas of helminth endemicity.…”
Section: Probiotic Bacteria and Helminth Infectionsupporting
confidence: 71%
“…Several studies have tried to investigate the possible role of probiotics in influencing the course of allergic pathologies such as AD, asthma, allergic rhinitis, and FAs [ 5 , 84 , 85 , 86 ]. Some studies have demonstrated the beneficial effect that probiotics have on AD; in particular, compared to a placebo, their administration caused a reduction of AD incidence and relieved AD symptoms, especially in children older than 1 year.…”
Section: Microbiotamentioning
confidence: 99%